2020
DOI: 10.1002/agj2.20119
|View full text |Cite
|
Sign up to set email alerts
|

Winter canola response to soil and fertilizer nitrogen in semiarid Mediterranean conditions

Abstract: In the semiarid dryland wheat (Triticum aestivum L.) region of the U.S. inland Pacific Northwest, winter canola (WC) (Brassica napus L.) is an economically viable rotation crop. Winter canola produces marketable end-products while improving soil health and disrupting pest and disease cycles. Although annual production of WC in Washington State has increased in the recent decade, little regional fertility research has been conducted. As a result, WC is commonly fertilized in a manner similar to hard red spring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Canola (Brassica napus L.) is the third most important source of vegetable oil after soybean [Glycine max (L.) Merr.] and corn (Zea mays L.) and the second-largest source of feed meal for animals after soybean in the United States (U.S. Canola is well adapted to semiarid environments because of its deep taproot system and a unique growth pattern, allowing the utilization of nutrients from a deeper soil profile and increasing resilience under extreme weather conditions (Porter et al, 2020). Compared to spring canola, winter canola has 20-30% and 50-100% higher yield potential in the semiarid southern Great Plains (Boyles et al, 2012) and the inland Pacific North West (Sowers, 2018) of the United States, making it a promising alternative rotational crop for semiarid regions.…”
Section: Introductionmentioning
confidence: 99%
“…Canola (Brassica napus L.) is the third most important source of vegetable oil after soybean [Glycine max (L.) Merr.] and corn (Zea mays L.) and the second-largest source of feed meal for animals after soybean in the United States (U.S. Canola is well adapted to semiarid environments because of its deep taproot system and a unique growth pattern, allowing the utilization of nutrients from a deeper soil profile and increasing resilience under extreme weather conditions (Porter et al, 2020). Compared to spring canola, winter canola has 20-30% and 50-100% higher yield potential in the semiarid southern Great Plains (Boyles et al, 2012) and the inland Pacific North West (Sowers, 2018) of the United States, making it a promising alternative rotational crop for semiarid regions.…”
Section: Introductionmentioning
confidence: 99%
“…Evening Primrose produced 54.4% less seed compared to Rapeseed, but differences in yield between the two species reduced when N fertilizer was applied, suggesting a lower ability of the Evening Primrose to grow under non-optimal N conditions when compared to Rapeseed. In experiments not directly comparing these species, a similar response to N was found in Evening Primrose [20,40], Canola [41,42], and Carinata [43]. Evening Primrose and Rapeseed usually show a similar total biomass production [44,45], thus the main reason for yield differences is likely due to a low harvest index of the Evening Primrose.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, different cultivars of winter canola or environments may require different N rates to attain optimal seed yields. Porter et al (2019) observed little effect of N on winter canola yields in Washington State, which were mainly affected by water availability and residual soil N concentrations. In Pakistan, Cheema et al (2001) observed significantly enhanced seed yield with increasing N…”
Section: Introductionmentioning
confidence: 80%
“…Porter et al. (2019) observed little effect of N on winter canola yields in Washington State, which were mainly affected by water availability and residual soil N concentrations. In Pakistan, Cheema et al.…”
Section: Introductionmentioning
confidence: 99%